Role of C9orf72 hexanucleotide repeat expansions in ALS/FTD pathogenesis - Geng, Yanyan; Cai, Qixu (Frontiers in Molecular Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are progressive neurological disorders that share neurodegenerative pathways and features. The most prevalent genetic causes of ALS/FTD is the GGGGCC hexanucleotide repeat expansions in the first intron region of the chromosome 9 open reading frame 72 (C9orf72) gene. In this review, we comprehensively summarize the accumulating evidences elucidating the pathogenic mechanism associated with hexanucleotide repeat expansions in ALS/FTD. These mechanisms encompass the structural polymorphism of DNA and transcribed RNA, the formation of RNA foci via phase separation, and the cytoplasmic accumulation and toxicities of dipeptide-repeat proteins. Additionally, the formation of G-quadruplex structures significantly impairs the expression and normal function of the C9orf72 protein. We also discuss the sequestration of specific RNA binding proteins by GGGGCC RNA, which further contributes to the toxicity of C9orf72 hexanucleotide repeat expansions. The deeper understanding of the pathogenic mechanism of hexanucleotide repeat expansions in ALS/FTD provides multiple potential drug targets for these devastating diseases.